Medical Informatics: Between Science and Engineering, Between Academia and Industry - Shahar, Y. (Methods of Information in Medicine, 2002)
Objective: To analyze the nature and appropriate role of the Medical Informatics research and practice area in the 21st Century, and to determine its links to academic environments versus industrial companies and health-care organizations.Methods: A qualitative analysis of the state of the art of Medical Informatics, based on observation of current medical informatics programs and research in academic and industrial sites.Results and Conclusions: Medical Informatics is definitely a scientific and technological area of endeavor, although somewhat ill-defined in scope. It is situated between science and engineering, but much closer to the engineering world, and its multidisciplinary nature fits well the engineering paradigm. It is better viewed as a specialization of the informatics field rather than as a basic medical science. However, there are good arguments as to why Medicine should be the first among equals to have its own informatics domain. Medical Informatics must have extensions to both academia and industry to survive. Medical informaticians, whether implicitly or explicitly, exist in three different environments: academic, clinical (user), and industrial (informatics developer); all three environments must be considered when trying to predict the future of this new multi-disciplinary area.
Keywords: Medical informatics; health care; informatics; health informatics education; health information systems; multidisciplinary research